Prevalence Of Tooth Injuries Among Children 2 To 13 Years Of Age Reporting To Dental Hospital- An Institutional Based Retrospective Study - FAREEN, H. FIRDUS; GURUNATHAN, DEEPA; RENGALAKSHMI, SRI. (The journal of contemporary issues in business and government, 2020)
Traumatic dental injuries present complex injuries of the dentoalveolar system. Trauma to primary and permanent teeth and their supporting structures is one of the most common dental problems seen in children. The purpose of this study was to analyse the prevalence of traumatic dental injuries (TDI) in primary and permanent teeth among childrens 2 to 13 years of age visiting the dental hospital in Chennai, in the period of June 2019 - March 2020. Date of age, gender, type of teeth i.e primary or permanent, type of dental injury and the dental treatment were obtained from the records of the dental hospital. The data was analysed using SPSS software. Chi Square Test was performed to compare two proportions. The analysis was done for: age, gender, type of injury, treatment done for the injury in this study. Most common type of dental injury in primary teeth is luxation (26.3%) and in permanent teeth is complicated crown fracture (38.9%). Traumatic dental injury was observed most frequently in the age group of 2 to 3 years in primary teeth and 10 to 11 years in permanent teeth with 68.4% and 69.4% of gender predliction in boys with primary and permanent dentition respectively. In the primary dentition, the most commonly performed treatment was extraction whereas the most common treatment performed in permanent dentition is pulpectomy. The results of this study show that emergency intervention to traumatised teeth is important for good prognosis of teeth and oral tissues. Therefore, the parents should be informed about dental trauma in schools and dental hospital physicians should be subjected to postgraduate training.